Explanation:
we multiply one of the equations (left and right) by a factor, so that either the x term or the y term are equal to the other equation.
and then we subtract one equation from the other.
4x - 2y = 4
2x + 6y = 16
for me the x terms immediately catch my eye.
so, I multiply the second equation by 2.
4x + 12y = 32
now for the subtraction :
4x - 2y = 4
- 4x + 6y = 16
---------------------
0 - 8y = -12
8y = 12
y = 12/8 = 3/2
=> in the first equation
4x + 2× 3/2 = 4
4x + 3 = 4
4x = 1
x = 1/4
so, the solution is (1/4, 3/2)